Bioquímica quântica do anti-hipertensivo losartan-sACE e do anti-inflamatório minoTc-PLA2 - Bezerra, Eveline Matias (2022)
It is known that the action of a drug is directly related to its chemical constitution. However, this claim was first noted only in 1868. Structure-based drug development is an important area of research where a detailed understanding of ligand-protein interactions is key to success. Thus, there is great interest in computational methods to predict and describe ligand-protein interactions. The three-dimensional conformation of the ligand (drug) is important for its interaction with the binding site of the protein. Therefore, the spatial distribution of the molecule’s structure defines how the binding site will be filled to have the potential to make intermolecular interactions with the amino acids of the site. Thus, a specific spatial configuration of the ligand in the receptor is necessary for the intermolecular interactions to be established. In the present thesis, a in silico study of two important systems was carried out: LST-sACE and minoTc-PLA2. The first study involves the angiotensin-converting enzyme (ACE) and was to study the interaction of the antihypertensive drugs lisinopril (LPR) and losartan (LST) with sACE through quantum biochemistry. Losartan (LST) is a potent and selective antagonist of the angiotensin II (Ang II) type 1 (AT1) receptor widely used in the treatment of hypertension. The formation of Ang II is catalyzed by the angiotensin I converting enzyme (ACE) through the proteolytic cleavage of angiotensin I (Ang I), which is involved in the control of blood pressure. Therefore, we investigated how losartan can interact with the sACE enzyme to block its activity and intracellular signaling. After performing molecular docking assays followed by quantum biochemistry calculations using crystallographic data from losartan and sACE, we conclude that their interaction results reveal a new mechanism of action with important implications for understanding their effects on hypertension. Then, it was evaluated how the homogeneous and non-homogeneous dielectric constants can influence the interaction energies of the lipophilic tetracycline minocycline with the enzyme phospholipase A2 (PLA2).